Ipsilateral hip abductor weakness after inversion ankle sprain - Friel, Karen; McLean, Nancy; Myers, Christine; Caceres, Maria (Journal of athletic training, 2006)
Hip stability and strength are important for proper gait mechanics and foot position during heel strike. To determine the relationships between hip muscle strength and chronic ankle sprains and hip muscle strength and ankle range of motion. Ex post facto design with the uninvolved limb serving as the control. Laboratory. A total of 23 subjects with unilateral chronic ankle sprain were recruited. Subjects had at least 2 ipsilateral ankle sprains and were bearing full weight, with the most recent injury occurring at least 3 months earlier. They were not undergoing formal or informal rehabilitation at the time of the study. We obtained goniometric measurements for all planes of motion at the ankle. Handheld dynamometry was used to assess the strength of the hip abductor and hip extensor muscles in both limbs. Hip abductor muscle strength and plantar flexion were significantly less on the involved side than the uninvolved side (P < .001 in each case). Strength of the involved hip abductor and hip extensor muscles was significantly correlated (r = 0.539, P < .01). No significant difference was noted in hip extensor muscle strength between sides (P = .19). Our subjects with unilateral chronic ankle sprains had weaker hip abduction strength and less plantar-flexion range of motion on the involved sides. Clinicians should consider exercises to increase hip abduction strength when developing rehabilitation programs for patients with ankle sprains.